2023
DOI: 10.1021/acsami.2c16592
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Navigated Biobot Swarms of Bacteria Magnetospirillum magneticum for Water Decontamination

Abstract: Hybrid biological robots (biobots) prepared from living cells are at the forefront of micro-/nanomotor research due to their biocompatibility and versatility toward multiple applications. However, their precise maneuverability is essential for practical applications. Magnetotactic bacteria are hybrid biobots that produce magnetosome magnetite crystals, which are more stable than synthesized magnetite and can orient along the direction of earth’s magnetic field. Herein, we used Magnetospirillum magneticum strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…This strategy combines the autonomous self-propulsion capabilities of the bacteria with controlled magnetic actuation to achieve precise motion control. [9] In addition to utilizing natural MTB, Pouponneau et al suggested integrating magnetosomes from magnetic-repellent bacteria with other bacteria. [117] These magnetosomes can serve as a means of propulsion for micro/nanorobots and other microscale entities.…”
Section: Bacteria-based Microrobot Swarmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy combines the autonomous self-propulsion capabilities of the bacteria with controlled magnetic actuation to achieve precise motion control. [9] In addition to utilizing natural MTB, Pouponneau et al suggested integrating magnetosomes from magnetic-repellent bacteria with other bacteria. [117] These magnetosomes can serve as a means of propulsion for micro/nanorobots and other microscale entities.…”
Section: Bacteria-based Microrobot Swarmsmentioning
confidence: 99%
“…Swimming micro/nanorobots can be designed to carry out various tasks that macroscopic robots cannot, which renders them more possibility to be applied in various fields, [1] including iatrology, [2][3][4][5][6] biology, [7,8] environment science, [9][10][11] and nanotechnology. [12,13] Especially in iatrology, these micro/nanorobots are expected to access hard-to-reach areas of the human body in a minimally invasive manner, such as the circulatory system, gastrointestinal tract, vasculature, brain, and eyes, [3,[14][15][16] resulting in the promising potential of micro/nanorobots for various biomedical applications, including targeted drug delivery, [17,18] cancer treatment, [19,20] diagnosis and monitoring, [21,22] minimally invasive surgery, [23,24] and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, they also used magnetotactic bacteria, Magnetospirillum magneticum strain AMB-1 ( M. magneticum AMB-1), as the building blocks for a microrobot swarm. 204 By applying a magnetic field, the bacteria would be synchronized and move in a swarm manner, which is due to the biosorption property with each other (but the mechanism wasn't thoroughly revealed). Nevertheless, compared to the popularity of the study in micro-/nanorobot swarms, the cases that focus on the influence of chemical and biological properties are still very rare, and the importance may be underestimated.…”
Section: Applications In Sensingmentioning
confidence: 99%
“…Inspired by these natural phenomena, researchers have developed micro/nanomotors with diverse driving forces to collaboratively tackle complex tasks. Over the years, various energy sources, including magnetic force [13][14][15][16][17][18][19], gradient energy [1,3,[20][21][22][23][24], and ultrasonic energy [25][26][27][28][29][30][31][32][33], have been employed to power these motors. Ultrasonic energy, in particular, is promising due to its non-invasive nature, causing no harm to organisms, and its ability to operate without physical contact.…”
Section: Introductionmentioning
confidence: 99%